UPAYA PENINGKATAN MUTU PEMBELAJARAN MELALUI SUPERVISI AKADEMIS PADA SDN 05 SUNGAI JAMBU KECAMATAN PARIANGAN KABUPATEN TANAH DATAR - HERI NOVERITA (STKIP Pesisir Selatan, 2019)
This study aims to improve teacher performance in carrying out learning activities through academic supervision at SDN 05 Sungai JambuKec. Pariangan Tanah Datar District. The School Action Research Study (PTS) is considered relevant in order to improve teacher performance in carrying out learning activities to improve the quality of education. This study uses an observation method and an assessment instrument that contains 30 items implementing learning activities used during the observation activities. The results of the assessment are then analyzed and used as material for action planning in the next cycle, in order to draw conclusions. School Action Research Findings (PTS) after analysis shows that based on preliminary observations on SDN 05 Sungai Jambu, ParianganSubdistrict, Tanah Datar, the average value is 50%. After carrying out the first cycle an average value of 73% was obtained. While the implementation of the second cycle obtained an average value of 89%. Implications of the results of School Action Research (PTS) through academic supervision can improve teacher performance in carrying out learning activities at SDN 05 Sungai Jambu, Pariangan District, TanahDatar District.